2014
DOI: 10.1021/ja504137u
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in Elastomeric Nanoreactors Reveal the Role of Force on the Kinetics of the Huisgen Reaction on Surfaces

Abstract: The force dependence of the copper-free Huisgen cycloaddition between an alkyne and a surface-bound azide was examined in elastomeric nanoreactors. These studies revealed that pressure and chain length are critical factors that determine the reaction rate. These experiments demonstrate the central role of pressure and surface structure on interfacial processes that are increasingly important in biology, materials science, and nanotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…Recently,h igh pressure has been successfully employedi nf acilitating organic reactions, such as polymerization of butadiyne, [11] acetylene, [12] cyanoacetylene, [13] and some other systems. [14] Yet, the application of crystal engineering and pressure in aw ider scope of reactions in the solid state is highly favorable to be explored. Our group has previously developed the first [15] metal-free azide-alkyne cycloaddition (AAC)p olymerization with 1,4-regioselectivity by prearrangement of the azide and alkyne functional groups through arene-perfluoroarene interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,h igh pressure has been successfully employedi nf acilitating organic reactions, such as polymerization of butadiyne, [11] acetylene, [12] cyanoacetylene, [13] and some other systems. [14] Yet, the application of crystal engineering and pressure in aw ider scope of reactions in the solid state is highly favorable to be explored. Our group has previously developed the first [15] metal-free azide-alkyne cycloaddition (AAC)p olymerization with 1,4-regioselectivity by prearrangement of the azide and alkyne functional groups through arene-perfluoroarene interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, they showed that it was possible to obtain patterns in water, which represented a significant advance for linear cantilever‐based architectures. Being able to pattern in liquids with cantilever‐free BPL pen arrays would be a significant advance as well, since they are extremely inexpensive, easy to fabricate, massively parallel (millions of probes), independently addressable, and potentially useful for solid‐phase nanoscale reactions . In this work, we present a systematic study of BPL in liquid that evaluates how the parameters such as tip‐substrate gap and aperture size affect patterning performance.…”
mentioning
confidence: 99%
“…When resorcinarene (0.05 molar ratio) was added at 0 h, Figure S1 shows the lag time is approximately 9 h. However, when the same amount of resorcinarene was added at time 1 h and 2 h, the lag phase shrink to 4 h and 3 h, respectively, which strongly indicates resorcinarene is likely to interact with insulin at the early stage of nucleation. During this lag phase, resorcinarene created an unfavorable entropical changes, which in turn disrupted the elongation step . (Table S2) To clarify if the inhibition effect is associated with micelles of the conjugated molecules, dynamic light scattering (DLS) was employed to examine the size of different resorcinarene inhibitors.…”
Section: Figurementioning
confidence: 99%
“…During this lag phase, resorcinarene createda nu nfavorable entropical changes, which in turn disrupted the elongation step. [18] (Table S2) To clarify if the inhibition effect is associated with micelles of the conjugatedm olecules, dynamic light scattering (DLS) was employed to examine the size of different resorcinarene inhibitors. As ar esult, the disruption to the insulin amyloid formation is achievedb ya single molecule insteado fc lusters.…”
mentioning
confidence: 99%